Elita polityczna Wielkopolski w epoce stanisławowskiej = The political elite of the Greater Poland during the reign of Stanisław August Poniatowski - Stroynowski, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper, related to regional research, is devoted to the region of Greater Poland in the period of the reign of Stanisław August Poniatowski and its political elite comprising high rank officials: bishops, voivods, castellans and the general Starost. The presentation is based on biographical entries, lists of officials, parliamentary documents and diaries. Particular focus is put on the characteristic features of the elite which over the period of thirty years consisted of 52 persons some of whom occupied various positions on several occasions.
Keywords: Wielkopolska - historia - 18 w.; elita polityczna; Poniatowski, Stanisław August (król polski; 1732-1798)